Changing prevalence and treatment of depression among older people over two decades. (January 2020) - Arthur, Antony; Savva, George M.; Barnes, Linda E.; Borjian-Boroojeny, Ayda; Dening, Tom; Jagger, Carol; Matthews, Fiona E.; Robinson, Louise; Brayne, Carol
Abstract : Background: Depression is a leading cause of disability, with older people particularly susceptible to poor outcomes. Aims: To investigate whether the prevalence of depression and antidepressant use have changed across two decades in older people. Method: The Cognitive Function and Ageing Studies (CFAS I and CFAS II) are two English population-based cohort studies of older people aged ≥65 years, with baseline measurements for each cohort conducted two decades apart (between 1990 and 1993 and between 2008 and 2011). Depression was assessed by the Geriatric Mental State examination and diagnosed with the Automated Geriatric Examination for Computer-Assisted Taxonomy algorithm. Results: In CFAS I, 7635 people aged ≥65 years were interviewed, of whom 1457 were diagnostically assessed. In CFAS II, 7762 people were interviewed and diagnostically assessed. Age-standardised depression prevalence in CFAS II was 6.8% (95% CI 6.3–7.5%), representing a non-significant decline from CFAS I (risk ratio 0.82, 95% CI 0.64–1.07, P = 0.14). At the time of CFAS II, 10.7% of the population (95% CI 10.0–11.5%) were taking antidepressant medication, more than twice that of CFAS I (risk ratio 2.79, 95% CI 1.96–3.97, P < 0.0001). Among care home residents, depression prevalence was unchanged, but the use of antidepressants increased from 7.4% (95% CI 3.8–13.8%) to 29.2% (95% CI 22.6–36.7%). Conclusions: A substantial increase in the proportion of the population reporting taking antidepressant medication is seen across two decades for people aged ≥65 years. However there was no evidence for a change in age-specific prevalence of depression.